Knowledge Level and Beliefs of Mothers of Children Under 5 Years of Age About Childhood Vaccinations - Turhan Aksoku, Berna; Aypak, Cenk; Güven, Deniz (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Vaccination prevents infectious diseases and mother’s consent is key to increasing childhood vaccination rates. The aim of this study was to assess mothers' knowledge, and beliefs about childhood vaccinations, as well as the impact of these factors on their vaccination behaviors. A descriptive cross-sectional study of 320 mothers was conducted. The data were collected using a questionnaire form. Most of mothers (98.4%) have their children fully vaccinated through the Extended Immunization Program (EIP), 96.6% of cases support vaccines necessity. Vaccine hesitancy was 7.8%, vaccine refusal was 1.6%. The majority of mothers believe that the most common side effects of vaccines are fever (53.4%). Mothers were not adequately informed about EIP were 42.2%, and 57.5% of them had not received non-EIP vaccines, and 33.1% cited lack of knowledge as the reason. The majority of cases (73.7%) received information about EIP from a doctor. Parents' educational status, higher family income, and having more than three children significantly increased non-EIP vaccination rates but had no significant effect on EIP vaccination (p<0.05). Mothers still support EIP, but vaccine hesitancy is growing due to a lack of information. It is critical to assess mothers' knowledge and beliefs about vaccination, and social awareness is also required.